Musical Creation Uma Yuga | Tabuh Kreasi Uma Yuga - Wayan Aldy Arya Hartawan (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Efforts to protect rice fields from land conversion, sanctity and preservation of Subak as a traditional institution imbued with supporting the existence of Balinese Culture by Hinduism, for community members who desecrate the sanctity of rice fields, will be given appropriate sanctions. The author wants this article to exist in the eyes of people who see rice fields in one eye. A humanist named I Gede Anom Ranuwara emphasized that